Comparative Analysis in the Teaching of Educational Trends Mediated by ICT in Higher Education (Docentes 2.0 Journal, 2024)
Education is fundamental to achieving a better quality of life and improving social welfare, from which communities' cultural, social, and economic growth is generated. The objective of this research was to make a comparative analysis of the educational trends in the use of ICT carried out by the educational program students. It was based on the comparative method under the pragmatic paradigm with a mixed approach: the quantitative analysis of the statistical results of the educational intervention and the qualitative analysis to know the degree of satisfaction through a survey applied to the students. The students who participated were 34; 22 were assigned to CUCEA and 12 to CUNorte. The methodology used was comparative education, which allowed for the analysis of where the times, contents, activities, teaching strategies, and use of technological tools were determined. The results are presented in two aspects: the first, carried out by the two work groups, reflecting the similarities with high achievement reflected in the percentage of attendance, general participation, and the grades obtained; the second, in the high degree of satisfaction they expressed. With everything done, it was possible to conclude with the appreciation of a very encouraging experience, that is, being able to promote or motivate future teachers in diversifying educational practices supported by current educational trends and, consequently, a great impact on society.
Keywords: Learning; challenges; digital skills; educational trends